Kajian Literatur tentang Model dan Metode untuk Meningkatkan Kualitas Perkuliahan Analisis Real - Harahap, Ananda Aditya Sari; Hasanah, Rusi Ulfah; Sitorus, Siti Fatimah (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to find out empirically about models/methods to significantly improve the quality of analytical lectures. This research uses literature study research by examining 10 journals that are relevant to the author's research. The results of this research show that real analysis courses require students' critical thinking skills, to be able to make proof of the problems raised. For this reason, mathematics students must have the ability to carry out mathematical proofs. In mathematical proof, there are two abilities, namely the ability to read proof and construct proof.